ANALISIS KINERJA REKSA DANA SYARIAH SAHAM TAHUN 2009 - 2012 - , Noviana Soesanty ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Syariah mutual fund is an investment product with restrictions on its investment portfolio. Syariah Fund is able to generate optimal returns with a screening process. This study provides an overview of the performance of Syariah Equity Fund, in particular the feasibility of rate of return and risk as compared with the single index market returns (JII). Performance measurement of Syariah Equity Fund used measurement methods with parameters that are commonly used, namely Sharpe, Treynor and Jensen Measures, to investigate the performance of outperforming or underperforming mutual fund. In addition Snail Trail was also used to see the effort and ability of the Investment Manager portfolio consistently make low riskhigh return. Sharpe Index and Jensen Index in the period 2009-2012 shows 5 of 8 performance of Syariah Fund Shares that is above comparison. Treynor Index in the period 2009-2012 shows the performance of 6 of 8 Syariah Equity Fund were above the quote. By using Sharpe, Treynor and Jensen Measure, BNP Paribas Pesona Amanah Mutual Fund is in the first rank the best performance. With Snail Trail, Manulife Mutual Funds Sectoral Amanah Syariah ranks first for their efforts consistently maintaining its investment portfolio is in quadrant 1 and 2.